A Case of Solitary Nonvascularized Corneal Epithelial Dysplasia - Tomoya Morii; Takayoshi Sumioka; Ai Izutani-Kitano; Yukihisa Takada; Yuka Okada; Winston W.-Y. Kao; Shizuya Saika (Case Reports in Ophthalmological Medicine)
Background. Epithelial dysplasia is categorized as conjunctival/corneal intraepithelial neoplasia which is a precancerous lesion. The lesion is usually developed at the limbal region and grows towards central cornea in association with neovascularization into the lesion. Here, we report a case of isolated nonvascularized corneal epithelial dysplasia surrounded by normal corneal epithelium with immune histochemical finding of ocular surface tissues cytokeratins, for example, keratin 13 and keratin 12. Case Presentation. A 76-year-old man consulted us for visual disturbance with localized opacification of the corneal epithelium in his left eye. His visual acuity was 20/20 and 20/200 in his right and left eye, respectively. Slit lamp examination showed a whitish plaque-like lesion at the center of his left corneal epithelium. No vascular invasion to the lesion was found. The lesion was surgically removed and subjected to histopathological examination and diagnosed as epithelial dysplasia. Amyloidosis was excluded by direct fast scarlet 4BS (DFS) staining. Immunohistochemistry showed that the dysplastic epithelial cells express keratin 13 and vimentin, but not keratin 12, indicating that the neoplastic epithelial cells lacked corneal-type epithelium differentiation. Conclusions. The lesion was diagnosed as nonvascularized epithelial dysplasia of ocular surface. Etiology of the lesion is not known.